2017
DOI: 10.1128/jcm.00197-17
|View full text |Cite
|
Sign up to set email alerts
|

Target-Specific Assay for Rapid and Quantitative Detection of Mycobacterium chimaera DNA

Abstract: Mycobacterium chimaera is an opportunistic environmental mycobacterium belonging to the Mycobacterium avium-M. intracellulare complex. Although most commonly associated with pulmonary disease, there has been growing awareness of invasive M. chimaera infections following cardiac surgery. Investigations suggest worldwide spread of a specific M. chimaera clone, associated with contaminated hospital heater-cooler units used during the surgery. Given the global dissemination of this clone, its potential to cause in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(17 citation statements)
references
References 28 publications
2
15
0
Order By: Relevance
“…Real-time PCR detected M. chimaera DNA up to a concentration of 10 pg/μL; this result is comparable with the sensitivity (two genomic copies) reported by Zozaya-Valdés et al [ 29 ]. A DNA search using PCR will detect dead as well as live bacteria, however.…”
Section: Discussionsupporting
confidence: 87%
See 1 more Smart Citation
“…Real-time PCR detected M. chimaera DNA up to a concentration of 10 pg/μL; this result is comparable with the sensitivity (two genomic copies) reported by Zozaya-Valdés et al [ 29 ]. A DNA search using PCR will detect dead as well as live bacteria, however.…”
Section: Discussionsupporting
confidence: 87%
“…DNA extraction was performed by heat treatment. The real-time PCR protocol was adapted from Zozaya-Valdés et al [ 29 ] to detect a 79 bp fragment of the SR1 region, identified as highly specific for M. chimaera . The SR1 region target for the TaqMan assay was selected by aligning 96 mycobacterial genome sequences, including 63 M. chimaera sequences from different countries, and it was 100% conserved among all M. chimaera templates.…”
Section: Methodsmentioning
confidence: 99%
“…Some isolates will remain unclassifiable except using whole-genome sequencing patterns, which need to be determined. A new assay based on a simplex PCR has been recently described and could also be used in such a situation to rapidly identify M. chimaera [29]. The strengths of our study were to provide clinical validation of commercially available tools for M. chimaera identification and differentiation from M. intracellulare.…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial factors carried by mobile genetic elements may drive a common fitness advantage across different bacterial genetic backbones, irrespective of sequence type, as has been reported in recent Streptococcus pyogenes outbreaks ( 15 , 19 ), and as such, comparative analyses may yield important insight into intersequence-type bacterial outbreaks. Such targeted analyses can be applied to advance diagnostics and surveillance of key clones, as has been applied to Mycobacterium chimaera ( 20 ). The authors of this research speculate that the infected equine population lacked protective immunity to the outbreak strain, and this remains an interesting hypothesis.…”
Section: Commentarymentioning
confidence: 99%